The Development of Contextual Learning Based Textbook to Improve Students’ Critical And Creative Thinking Ability of Islamic Eduction Subject at MAN Surabaya - Arofah Rahmat (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
This study aimed to identify: (1) the validity of the developed contextual learning based textbook (2) practicality of the developed contextual learning based textbook (3) effectiveness of the developed contextual learning based textbook to improve students’ critical and creative thinking ability. This study used developement research design by adopting ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This study consisted of three stages: introduction, developement, and test of effetiveness. The validity result of textbook from 36 expert’s assessment items showed that 22 items were very suitable and 14 items were suitable. The textbook practicality was seen from checklist points achievement for contextual learning based textbook. The result of gain score analysis of students 'critical thinking ability was 0.769 or categorized as high, meaning that the use of contextual learning based textbook was effective to improve students' critical thinking ability. The result of gain score analysis of students 'creative thinking ability was 0.775 or categorized as high, meaning that the use of contextual learning based textbook was effective to improve students' creative thinking ability. Keywords: Textbook, Contextual learning, Critical Thinking, Creative Thinking.